Ethics-Based Educational Intervention by Religious Educators to Reduce Bullying Cases at SMP - Rohmat Hidayat; Chakam Abu Musa; Septian Ragil Anandita (SCHOOLAR: Social and Literature Study in Education, 2026)
Bullying in schools continues to be a pervasive issue that significantly impacts students' psychological, social, and academic development. At SMP Negeri 2 Perak Jombang, bullying manifests in various forms, including verbal, relational, and cyberbullying. This study explores the role of Islamic Education teachers in preventing and managing bullying using an ethics-based approach grounded in the principles of Islamic education. By adopting a descriptive-qualitative method, the research examines how Islamic Education teachers embody their roles as Mu’allim (knowledge providers), Mu’addib (ethical cultivators), and Murabbi (moral guides) to combat bullying. Through observation, interviews, and document analysis, the study finds that bullying often occurs in transitional spaces such as hallways and extends into digital platforms like WhatsApp groups. The research highlights that bullying is supported by social mechanisms, such as the normalization of derogatory humor and peer group reinforcement. The Islamic Education teachers, in their role as Mu’allim, educate students on values such as equality and respect, while as Mu’addib, they emphasize the importance of cultivating proper verbal etiquette and social ethics. As Murabbi, they provide ongoing guidance and collaborate with other school authorities to address bullying. The study concludes that ethics-based interventions by Islamic Education teachers, combined with collaborative efforts from guidance counselors, provide a robust model for bullying prevention, fostering a safer and more respectful school environment.